Posttranslational processing of an Epstein-Barr virus-encoded membrane protein expressed in cells transformed by Epstein-Barr virus. - Baichwal, V R (1987)
The BamHI Nhet fragment of the B958 strain of Epstein-Barr virus (EBV) encodes a membrane protein (BNLF-1) that is present in cells transformed by EBV. We made a hybrid protein in which a polypeptide sequence from the carboxyl-terminal part of BNLF-1 is fused to Escherichia coli beta-galactosidase. This hybrid protein was used to immunize rabbits, and the resulting antiserum was purified by immunoaffinity chromatography. The antiserum was able to immunoprecipitate BNLF-1 from cell lysates. We found that BNLF-1 is phosphorylated at serines in EBV genome-positive B-cell lines. Pulse-chase analyses with [35S]methionine indicated that BNLF-1 is turned over in lymphoblasts with a half-life of approximately 5 h. Protein immunoblots of EBV genome-positive B-cell lines revealed both a 62,000-molecular-mass band corresponding to BNLF-1 and a myriad of lower-molecular-mass bands. We postulate that these lower-molecular-mass bands are degradation products resulting from the turnover of BNLF-1 in cells. The BNLF-1 gene was expressed in COS cells, and the protein was both phosphorylated and turned over in these cells.